Pengaruh Reward Terhadap Kinerja Karyawan Pada PT. Agri Andalas - Widia Annisa Fitri; Harius Eko Saputra; Maryaningsih Maryaningsih (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study aims to determine the effect of reward on employee performance at PT. Agri Andalas Bengkulu Tengah. Reward is understood as a form of appreciation, either financial or non-financial, provided by the company as recognition of employees’ contributions. Meanwhile, employee performance is measured through indicators of quantity, quality, reliability, attendance, and teamwork ability. This research employs a quantitative approach with a population of 71 employees, all of whom were used as the sample through a total sampling technique. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. The data analysis techniques included descriptive analysis, Product Moment correlation, simple linear regression, and the coefficient of determination test.The results indicate that reward has a significant influence on employee performance, as evidenced by the correlation and t-test values that meet the significance criteria. This finding suggests that the better the reward system implemented by the company, the higher the performance demonstrated by employees. Therefore, the company is encouraged to improve the effectiveness of its reward policies—such as wages, salaries, bonuses, allowances, interpersonal recognition, and promotion opportunities—to support sustainable improvements in work productivity.